Authenticity and racism: young boys in three inner city primary schools in Dublin. Issue 9 (4th July 2022) - Garratt, Lindsey
ABSTRACT: This paper examines the role of authenticity as a moral orientation and social evaluation in practices of racism. It will argue that discursive conceptions of authenticity disguise and legitimise racism within micro encounters. Using evidence from a qualitative study of minority children in Ireland, this paper explores how perceptions of 'authenticity' are bound within racist and gendered conceptions of whom can be said to legitimately embody nationally and locally authorised dispositions and identity markers. The specific context of how this played out through the locality of north Dublin and constructed notions of Irishness is examined. The wider implications of a discourse of authenticity are discussed in relation to assumptions of similarity, adaptation and integration. This paper contributes two unique insights, firstly, that the passive body (one's appearance) has a central role in perceptions of authenticity and, secondly, that similarity in one's active body (dispositions and tastes) does not necessarily act as a bridge to bring racialised groups together or facilitate integration.